KEY DETERMINANTS OF CASH RESERVES IN MANUFACTURING FIRMS DURING COVID-19 IN INDONESIA: Cash Holding, COVID-19, Indonesian Stock Exchange, Manufacturing Firm - Cempaka, Santy Dwi; Hakim, Muhammad Saiful; Zharifa, Naila Qanita; Safitri, Ika; Jauhari, Muhammad Haris; Kunaifi, Aang (STIE PGRI Dewantara Jombang, 2024)
This study investigates the effects of the COVID-19 pandemic on cash reserves in Indonesian manufacturing companies. The research assesses cash levels before, during, and after the pandemic, and identifies key factors influencing cash holdings. Data from publicly listed manufacturing companies in Indonesia were analyzed, focusing on financial metrics such as earnings before interest, taxes, depreciation, and amortization (EBITDA), sales volatility, and net working capital. The findings reveal significant differences in cash, EBITDA, and sales volatility between the pre-crisis (2018-2019) and crisis periods horizons I (2020-2021) and II (2022). The primary determinants of cash holdings were found to be sensitivity of cash flow, capital expenditure, cash flow volatility, net working capital, and debt levels. These factors are crucial in understanding the impact of the pandemic on cash management in Indonesian manufacturing companies.